“EXPLORING THE MENTAL HEALTH LANDSCAPE: A CROSS-SECTIONAL ANALYSIS OF DEPRESSION, ANXIETY, AND STRESS IN RAJNANDGAON’S MEDICAL UNDERGRADUATES” - Dr. Nisha Meshram; Dr. Divya Sahu; Ms. Pallavi V. Gulhane (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- In the bustling corridors of Rajnandgaon’s medical college, a silent battle is being waged. The rigorous demands of medical education often cast a shadow over the mental well-being. The study seeks to shed light on this pressing issue. Aims: To assess the prevalence of depression, anxiety and stress among undergraduate medical students of Rajnandgaon, Chhattisgarh, India. Methods and Material: A cross-sectional study was conducted in this medical college during mid-semester 2023, involving 420 participants who gave written consent. DASS-21 scale was distributed through Google Forms via self -administered technique. Statistical analysis: IBM SPSS (version 20), was used to analyze Chi-square tests for association, Spearman’s correlation for inter-domain relationships, and Binary logistic regression to assess the factor influence on each other. Inter-domain’s comparisons and relationships visualized through Venn diagrams, while Line diagram showed the prevalence over time. Results: More than one fifth (20.48%) subjects were having all three psychological domains; needs to pay attention for the management. More than one fifth (24.51%) subjects were having stress, more than two fifth (40.93%) were having anxiety and near about two fifth (34.93%) were having depression. Conclusions: A significant prevalence of stress, anxiety, and depression among medical students, with nearly a quarter experiencing stress, over a third anxiety, and a similar proportion of depression. Notably, one in five students reported all three conditions. The higher prevalence especially among males, underscores the current mental health challenges. Urgently strict mental health screening and effective management during admission are necessary to address these issues.